A Novel Low Temperature Cofired-Cordierite Ceramic Substrate-Based Compact Ultra-Wideband Circularly Polarized Array Antenna for C-Band Remote Sensing Application - Pramono, Subuh; Sumantyo, Josaphat Tetuko Sri; Ibrahim, Muhammad Hamka; Takahashi, Ayaka; Yoshimoto, Yuki; Kashihara, Hisato; Santosa, Cahya Edi; Gao, Steven; Ito, Koichi (IEEE Open Journal of Antennas and Propagation, 2025)
This research proposes a novel antenna substrate that is realized based on low-temperature co-fired ceramic (LTCC) technology using cordierite ceramic (2MgO 2Al2O {_{{3}}}~5 SiO2). Compared to other existing ceramics, it has an impressive low dielectric constant \rm (ε _{r}) of 4.674 and a loss tangent (tan δ ) of 0.0723 at 5.3 GHz, which makes it ideal for creating an ultra-wideband (UWB) circularly polarized (CP) array antenna. In addition, cordierite ceramic is suitable for high-temperature environments, its coefficient of linear thermal expansion is about 1.8× 10{^{-}6 } /K (40°C- 800°C), and it expands only 0.1% of its room temperature dimensions even in a 1000°C environment. Through a sputtering process, platinum with a melting point of 1768°C and very good oxidation resistance is used as a conductive material on the cordierite ceramic substrate. Based on the measured results, the proposed 2× 2 CP array antennas have an ultrawide impedance bandwidth (IBW) of 1.74 GHz (32.83%), an axial ratio bandwidth (ARBW) of 1.26 GHz (23.77%), and a maximum gain of 12.2 dBic. In the experimental test, the proposed 2× 2 CP antennas are set up as transmitters and receivers in a CP synthetic aperture radar (SAR) system with full polarimetric modes (L-L, L-R, R-L, and R-R) for remote sensing applications. The transceiver 2× 2 CP array antennas have high isolation with an average mutual coupling level of around −65.9 dB. The back projection algorithm is applied to convert the received data into the scattering images and samples the maximum scattering intensities from the scattering images that are presented in scattering matrices. The measured scattering matrices have a similar trend to the theoretical scattering matrices. Based on the heat-exposed measurement, exposure to 500°C of heat on the 2× 2 CP array antennas causes physical change. The antennas expand in size, which leads to a slight shift in the center frequency by 140 MHz. This proves that the proposed 2× 2 CP array antennas perform well in high-temperature conditions.